Human sacrifice and value: revisiting the limits of sacred violence from an archaeological and anthropological perspective - Walsh, Matthew J.; O'Neill, Sean; Moen, Marianne; Gullbekk, Svein H.; Nilsson, Eva-Johanna Marie Lafuente (Studies in death, materiality and the origin of time, 2024)
"This volume explores concepts of human sacrifice, focusing on its value - or multiplicity of values - in relative cultural and temporal terms, whether sacrifice is expressed in actual killings, in ideas revolving around ritualized, sanctioned, or sanctified violence or loss, or in transformed and (often sublimated) undertakings"--